GLOBAL TRENDS AND THEMES IN SOCIAL AND EMOTIONAL LEARNING (SEL) COMPETENCIES AMONG EDUCATORS: A BIBLIOMETRIC ANALYSIS - Gazi, Abdul Karim; Ganasan, Marcia Jane; Yahaya, Mohamad Fadhili (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Educators’ Social and Emotional Learning (SEL) competencies foster a comprehensive teaching and learning process. This bibliometric analysis investigates the research landscape of lecturers’ SEL competencies over the last 25 years. Data are collected from Scopus and were analysed using MS Excel, Harzing’s Publish or Perish, and VOSviewer. A total of 151 papers were selected for analysis using PRISMA. The results of this study highlighted publication trends, influential contributors, key research areas, and international collaborations in SEL. The number of publications related to SEL competencies rose sharply after 2020, peaking at 32 papers in 2024. The United States takes the lead in research contributions with 99 papers, followed by Canada and other countries across Europe and Asia. The concentration of SEL research in Social Sciences (128 papers) and Psychology (59 papers) illustrates a wide-ranging interdisciplinary relevance in SEL. SEL research indicates key themes include emotional intelligence, classroom management, student engagement, equity, and mental health. The widely cited works of Hellman & Milling (2020) and Mondi & Reynolds (2021) underscore the importance of SEL in education and early intervention studies. Co-authorship and co-citation analyses demonstrate active collaborative networks among scholars and institutions such as Arizona State University. Keyword co-occurrence analyses further revealed emerging trends like social justice, inclusion, and the integration of SEL into digital and culturally responsive educational practices. The study further suggests that it is essential to cultivate an SEL-supportive learning environment through educator SEL skills and techniques.